2020
DOI: 10.1089/dna.2020.5423
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Anti-Atrophic Effects of Leucine Involve Myostatin Inhibition

Abstract: Lack of mechanical load leads to skeletal muscle atrophy, and one major underlying mechanism involves the myostatin pathway that negatively regulates protein synthesis and also activates Atrogin-1/MAFbx and MuRF1 genes. In hindlimb immobilization, leucine was observed to attenuate the upregulation of the referred atrogenes, thereby shortening the impact on fiber cross-sectional area, nonetheless, the possible connection with myostatin is still elusive. This study sought to verify the impact of leucine suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 57 publications
3
10
0
Order By: Relevance
“…As mentioned, silent mutations of G>A in leucine (Leu) amino acid were found in this study. The investigation about the Leucine effect on Myostatin expression on skeletal muscles of Wistar rats (Cruz et al;2020) demonstrated and confirm the importance of Leucine. They have found leucine prevents the loss of skeletal muscle mass and causes a decrement in the Myostatin expression, even block it in some circumstances (Cruz et al;2020).…”
Section: Figure 3 the Silent Mutation As G4183919 G>a In The Second E...supporting
confidence: 56%
See 1 more Smart Citation
“…As mentioned, silent mutations of G>A in leucine (Leu) amino acid were found in this study. The investigation about the Leucine effect on Myostatin expression on skeletal muscles of Wistar rats (Cruz et al;2020) demonstrated and confirm the importance of Leucine. They have found leucine prevents the loss of skeletal muscle mass and causes a decrement in the Myostatin expression, even block it in some circumstances (Cruz et al;2020).…”
Section: Figure 3 the Silent Mutation As G4183919 G>a In The Second E...supporting
confidence: 56%
“…The investigation about the Leucine effect on Myostatin expression on skeletal muscles of Wistar rats (Cruz et al;2020) demonstrated and confirm the importance of Leucine. They have found leucine prevents the loss of skeletal muscle mass and causes a decrement in the Myostatin expression, even block it in some circumstances (Cruz et al;2020). Since leucine alters the Myostatin expression and synonymous mutations can affect the amino acid and lead to several alterations as mentioned above, it can be interpretable that silent mutation in leucine in this study may affect the MSTN gene expression.…”
Section: Figure 3 the Silent Mutation As G4183919 G>a In The Second E...supporting
confidence: 56%
“…Leucine is able to stimulate the activation of proteins that are involved in regulating muscle protein synthesis. In this regard, Cruz et al (2020) evaluated the effect of leucine supplementation with hindlimb immobilized for 3 and 7 days, and reported significantly upgraded serum concentrations of follistatin and decreased serum concentrations of myostatin in male Wistar rats. Verhoeven et al (2009) found that 12 weeks of 3 gr of leucine supplementation did not significantly increase MPS in healthy elderly men.…”
Section: Discussionmentioning
confidence: 99%
“…The probable mechanism of soy milk on serum concentrations of follistatin, myostatin, GDF11, and also MFR, is yet unclear. Leucine, a component of soy milk, has an important role in maintaining and increasing muscle mass during the aging process (Cruz et al, 2020). Also, it has been indicated that leucine can minimize the muscle mass in injury, cachexia, cancer, and immobilization in older individuals (Cruz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation